2017
DOI: 10.1186/s40101-017-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular function during knee extension exercise after cold water immersion

Abstract: BackgroundHuman adaptability to cold environment has been focused on in the physiological anthropology and related research area. Concerning the human acclimatization process in the natural climate, it is necessary to conduct a research assessing comprehensive effect of cold environment and physical activities in cold. This study investigated the effect of cold water immersion on the exercise performance and neuromuscular function during maximal and submaximal isometric knee extension.MethodsNine healthy males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…of the Wingate test with cooling suit recovery (7 °C). Other studies have already shown decreased MF values after cooling intervention [ 45 , 48 ]. According to Herrera et al [ 49 ], reduced muscular temperature derived from cooling methods may be associated with slower nerve conduction velocity, which could increase the duration of action, potentially affecting the MF values.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…of the Wingate test with cooling suit recovery (7 °C). Other studies have already shown decreased MF values after cooling intervention [ 45 , 48 ]. According to Herrera et al [ 49 ], reduced muscular temperature derived from cooling methods may be associated with slower nerve conduction velocity, which could increase the duration of action, potentially affecting the MF values.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding acute cooling intervention applied before exercise, studies have reported decreased muscle activation (EMG amplitude) in response to the cold intervention [ 45 , 46 ]. Other investigators reported no significant changes [ 47 ] or increased muscle activation [ 48 ]. Differences relative to muscle contractions, cooling methods, cooling temperatures, and anatomical sites of cooling intervention seem to explain contradictory results among several studies.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that a decrease in temperature, induced by cryotherapy, could cause changes within the CNS, leading to a decrease in muscle activity [18]. Regarding the RMS of EMG, there has been more variable observation in references which reported increased or decreased amplitudes in cold environment [16]. This disagreement could be explained by different protocols including exercise type, cooling procedure, and selected muscle groups.…”
Section: Effects Of Cold Water Immersion On Recovery After a Karate Kmentioning
confidence: 83%
“…In detail, the effect of CWI on the muscle activation was more clearly observed in the RF compared to the VM and VL. Probably, the greater percentage of the fast twitch fiber in VM and VL rather than in the RF [16] and might explain this observation. Also this finding can be explained by difference in cooling the superficial (RF) and deep muscles (VL and VM).…”
Section: Effects Of Cold Water Immersion On Recovery After a Karate Kmentioning
confidence: 84%
“…; Petrofsky and Laymon ; Wakabayashi et al. ) and is associated with a reduction of the muscle conduction velocity (Bigland‐Ritchie et al. ).…”
Section: Introductionmentioning
confidence: 99%